Ketentuan Hukum tentang Pembajakan Film dalam Perspektif Hak Cipta di Indonesia (Neolectura, 2023)
The development of the world of film is an important part of the entertainment industry, which continues to evolve and grow. Every day, there are new developments with unlimited ideas. Especially in Indonesia, the Indonesian film industry continues to increase every year and produces various works of various qualities. However, along with their development, works such as films are often used unwisely, and many people do not respect other people's works by committing piracy. In this journal, the author chooses to apply the normative juridical method with a conceptual approach and a statutory approach. Based on the results of the discussion, the authors can conclude that with advances in technology and knowledge, copyright law has also regulated new regulations regarding copyright infringements that occur through digital technology, as previously mentioned. This regulation was created in the formulation of Article 54 of the Copyright Law. The article contains a statement stating that